The Effect of Intrinsic Motivation on Innovative Work Behavior with Knowledge Sharing as a Mediating Variable - Wijaya, Selfi Atma; Syahrizal, Syahrizal (Human Resource Management Studies, 2024)
Innovative work behavior is one of the practices that is often researched in Human Resource Management (HRM) literature, intrinsic motivation and knowledge sharing are important managerial practices to research. Yet the relationship between these practices has received little attention in the literature. Therefore, this research aims to examine the influence of intrinsic motivation on innovative work behavior with knowledge sharing as a mediating variable. This research is causal research. The sampling technique was taken using total sampling where the number of samples was the same as the population, namely 105 people. Data collection used a questionnaire with a Likert scale. The analysis technique used is SEM using SmartPLS4 analysis. The results of data processing in the research show that intrinsic motivation has a positive and significant effect on innovative work behavior through sharing knowledge.